Introduction to social research : quantitative & qualitative approaches - Punch, Keith (Los Angeles, California : SAGE, 2014)
In the new edition of Introduction to Social Resarch, Keith Punch takes a fresh look at the entire research process, from formulating a research question to writing up your research.
Introduction -- Theory and method in social science research -- Ethics in social science research -- Research questions -- From research questions to data -- Literature searching and reviewing -- Qualitative research design -- Collecting qualitative data -- Analysing qualitative data -- Quantitative research design -- Collecting quatitative data -- Analysing quantitative data -- The internet and research -- Mixed methods and evaluation -- Research writing.
Previous edition: 2005.
Includes bibliographical references and index.
Keywords: Social sciences -- Research